Peningkatan Literasi Bahasa Indonesia untuk Menghindari Ujaran Kebencian dan Perundungan Bagi Siswa/Siswi MAN Binjai - Mulyadi, Mulyadi; Nasution, Ikhwanuddin; Dardanila, Dardanila; Widayati, Dwi (Universitas Pahlawan Tuanku Tambusai, 2024)
Nowadays, the function of language as a means of conveying messages to establish social interaction is somewhat neglected. Language is no longer a message, but has changed into a sentiment. This is represented in the form of hate speech and bullying that often occurs on social media by violating the Electronic Information and Transactions Law (UU ITE). The purpose of this community service activity is to increase knowledge and skills about the form of hate speech and bullying texts in Indonesian language literacy for students and also knowledge about the right procedures or strategies to avoid hate speech and verbal bullying by others. In this training, two methods were applied, namely practice and simulation. The results of the community service activities showed that students experienced a significant increase in Indonesian language literacy to avoid hate speech and bullying. Before the delivery of the material, students scored 4,594. However, after the delivery of the material, there was an increase in student scores, namely 4,640. This increase illustrates the effectiveness of the activity program. Students experienced significant progress in terms of understanding or skills as measured by pretest and posttest.